What old stagers could teach us: Examining age complementarities in regional innovation systems - Melanie Arntz; Terry Gregory (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Concerns have been raised that demographic ageing may weaken the competitiveness of knowledge-based economies and increase regional disparities. The age-creativity link is however far from clear at the aggregate level. Contributing to this debate, we estimate the causal effect of the workforce age structure on patenting activities for local labour markets in Germany using a flexible knowledge production function and accounting for potential endogeneity of the regional workforce structure. Overall, our results suggest that younger workers boost regional innovations, but this effect partly hinges on the presence of older workers as younger and older workers turn out to be complements in the production of knowledge. With demographic aging mainly increasing the older workforce and shrinking the younger one, our results imply that innovation levels in ageing societies may drop in the future. Moreover, differences in the regional age structure currently explain around a sixth of the innovation gap across German regions.
urn:nbn:de:bsz:180-madoc-369395
Keywords: R12; R23; J11; 330; regional innovation system; demographic ageing; knowledge production function; regional disparities; age complementarities